Leveraging economic intelligence and stakeholder collaboration to eradicate illegal plain cigarettes - Indradinata, Bayu; Samputra, Palupi Lindiasari; Salya, Sundawan (Ex Aequo Et Bono Journal Of Law, 2025)
Background: Indonesia ranks third globally in the number of smokers, despite government efforts to reduce cigarette consumption. The continued rise in smoking is linked to the circulation of illegal cigarettes, which threaten public health, state revenue, and the national tobacco industry. This study aims to examine the distribution dynamics of illicit cigarettes and analyze stakeholder strategies to combat the issue. Methods: A qualitative approach was used, involving interviews, document analysis, and literature review. Data were analyzed thematically to explore patterns in stakeholder roles and motivations. Findings: Economic incentives drive the illegal cigarette trade, which disrupts legal markets and undermines tax revenue. Stakeholder participation varies by institutional interest and authority, influencing enforcement outcomes. Weak coordination and limited use of economic intelligence were identified as key challenges. Conclusion: Addressing illegal cigarette distribution requires stronger stakeholder collaboration and strategic use of economic intelligence. Novelty/Originality of this article: This study provides new insights into the role of economic intelligence and stakeholder dynamics in tackling illicit cigarette trade in Indonesia.